Cancer Risk Assessment and Screening; A Challenge for Clinical Pathology Service? - Siti Boedina Kresno (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
There is evidence demonstrating that cancer etiology is multi-factorial and modification of risk factors has achievedcancer prevention. There is therefore a need to advance the understanding of cancer etiology through interaction effectsbetween risk factors when estimating the contribution of an individual to the cancer burden in a population. It has beenknown that cancer may arise from genetic susceptibility to the disease as an intrinsic factor; however, non-intrinsic factorsdrive most cancer risk as well and highlight the need for cancer prevention. Are our clinical pathologists aware of thesefacts?. Are they ready to understand and to provide an excellent test with good expertise?. Hereditary cancer testing istypically performed using gene panels, which may be either cancer-specific or pan-cancer to assess risk for a defined orbroader range of cancers, respectively. Given the clinical implications of hereditary cancer testing, diagnostic laboratoriesmust develop high-quality panel tests, which serve a broad, genetically diverse patient population. The result will determinea patient's eligibility for targeted therapy, for instance, or lead a patient to prophylactic surgery, chemoprevention, andsurveillance. This review will introduce the definitions of intrinsic and non-intrinsic risk factors, which have been employed inrecent work and how evidence for their effects on the cancer burden in human subjects has been obtained. Genetic testingof cancer susceptibility genes by use of liquid biopsies and New Generation Sequencing (NGS) is now widely applied inclinical practice to predict the risk of developing cancer, help diagnosis, and treatment monitoring.